PERSEPSI GURU SEKOLAH DASAR JAKARTA UTARA TERHADAP MITIGASI BENCANA BANJIR - Yustia Suntari (Jurnal Pendidikan Dasar, 2018)
Abstract: This study aims to determine how the perception of elementary school teachers in North Jakarta on flood disaster mitigation. A flood that often occurs in Jakarta, the capital of Indonesia, should be anticipated and dealt with jointly between the government and the community. Flood disasters that are detrimental to both materially and non materially should be given the main attention of all parties and should be taught to students, so that flood prevention can be faster and more precise. This research is a type of survey research with a quantitative descriptive approach. This survey study aims to describe the perceptions of elementary school teachers on flood disaster mitigation and their understanding of disaster mitigation education. The results of this study state that all elementary school teachers in the North Jakarta area who are affected by rob water state that they have never provided a simulation to their students regarding the way to deal with flood water. Although 35% of respondents stated that they had received a flood prevention simulation. Simulations that have been given are only intended for adults, not for elementary school age children. Most teachers have also taught material about disasters, but only a few have specifically discussed rob floods. Keyword : Perception of Elementary Teachers, Disaster Mitigation